ROSYJSKI KANON – W SZWEDZKIEJ PERSPEKTYWIE (Per-Arne Bodin, Language, Canonization and Holy Foolishness. Studies in Postsoviet Russian Culture and the Orthodox Tradition . Stockholm University, Stockholm 2009, pp. 326) - Bakuła, Bogusław (Porównania, 2012)
ROSYJSKI KANON – W SZWEDZKIEJ PERSPEKTYWIE